Kolmogorov widths of weighted Sobolev classes with “small” singularity sets - Vasil’eva, Anastasia (Eurasian Mathematical Journal, 2019)
Sharp order estimates are stated for the Kolmogorov widths of weighted Sobolev classes on h-sets for certain limiting cases of the parameters.